miR-148a-3p Mediates Notch Signaling to Promote the Differentiation and M1 Activation of Macrophages - Huang, Fei; Zhao, Jun-Long; Wang, Liang; Gao, Chun-Chen; Liang, Shi-Qian; An, Dong-Jie; Bai, Jian; Chen, Yan; Han, Hua; Qin, Hong-Yan (Frontiers in Immunology, 2017)
The Notch pathway plays critical roles in the differentiation and polarized activation of macrophages; however, the downstream molecular mechanisms underlying Notch activity in macrophages remain elusive. Our previous study has identified a group of microRNAs that mediate Notch signaling to regulate macrophage activation and tumor-associated macrophages (TAMs). In this study, we demonstrated that miR-148a-3p functions as a novel downstream molecule of Notch signaling to promote the differentiation of monocytes into macrophages in the presence of granulocyte macrophage colony-stimulating factor (GM-CSF). Meanwhile, miR-148a-3p promoted M1 and inhibited M2 polarization of macrophages upon Notch activation. Macrophages overexpressing miR-148a-3p exhibited enhanced ability to engulf and kill bacteria, which was mediated by excessive production of reactive oxygen species (ROS). Further studies using reporter assay and Western blotting identified Pten as a direct target gene of miR-148a-3p in macrophages. Macrophages overexpressing miR-148a-3p increased their ROS production through the PTEN/AKT pathway, likely to defend against bacterial invasion. Moreover, miR-148a-3p also enhanced M1 macrophage polarization and pro-inflammatory responses through PTEN/AKT-mediated upregulation of NF-κB signaling. In summary, our data establish a novel molecular mechanism by which Notch signaling promotes monocyte differentiation and M1 macrophage activation through miR-148a-3p, and suggest that miR-148a-3p-modified monocytes or macrophages are potential new tools for the treatment of inflammation-related diseases.